A new classification for mandibular defects after oncological resection. Issue 1 (January 2016) - Brown, James S; Barry, Conor; Ho, Michael; Shaw, Richard
Summary: No universally accepted classification system exists for mandibular defects after oncological resection. Here, we discuss the scientific literature on classifications for mandibular defects that are sufficiently presented either pictorially or descriptively, and propose a new classification system based on these findings. Of 167 studies included in the data analysis, 49 of these reports sufficiently described the defect for analysis. These reports were analysed for classification, reconstruction, size of defect, number of osteotomies needed, and complications. On the basis of these findings, a new classification is proposed based on the four corners of the mandible (two angles and two canines): class I (lateral), class II (hemimandibulectomy), class III (anterior), and class IV (extensive). Further classes (Ic, IIc, and IVc) include condylectomy. The increasing defect class relates to the size of the defect, osteotomy rate, and functional and aesthetic outcome, and could guide the method of reconstruction.